Atomic force microscopy tip characteriser based on the fabrication of nanorod array structures. (1st December 2013) - Chen, Yuqin; Han, Guoqiang; He, Bingwei
Abstract : An atomic force microscopy (AFM) image is acquired by probe tip scanning on the surface of a sample. It is a distorted representation of the sample because of the finite size of the tip. To modify the distorted image and improve the measurement accuracy of the AFM image, it is important to estimate the tip shape. Tip estimation results mainly rely on the sample‐dimensional uncertainty and AFM image noise. More reliable data of tip morphology can be collected if there is a suitable tip characteriser to reduce the sample‐dimensional uncertainty and improve AFM image accuracy. A new tip characteriser for blind reconstruction of AFM tip morphology has been developed through the fabrication of gold nanorod array structures. Based on template synthesis, the gold film (surface roughness, 162.1 nm) was deposited on porous anodic alumina membrane by magnetron sputtering. The well‐ordered nanorod array structures (100–400 nm height, 60 nm diameter, ∼20 nm at apex and 80 nm pitch) were obtained. In combination with the blind reconstruction algorithm, the prepared nanostructures were used as the tip characteriser to estimate the morphology of the traditional AFM Si3 N4 probe, which can effectively reduce the influence of the sample‐dimensional uncertainty and image noise on the result of the tip blind reconstruction.